2021
DOI: 10.1002/fsn3.2594
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of selenium‐enriched peptides from soybean in cyclophosphamide‐induced immunosuppressed mice

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 82 publications
0
29
0
Order By: Relevance
“…IgM and IgG, secreted by B cells, are two key effector molecules in the humoral immune response. IgM exhibits a strong anti-infectious effect, while IgG participates in the phagocytosis of monocytes ( Zhang et al, 2021 ). T lymphocytes are important immune cells involved in the regulation of cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…IgM and IgG, secreted by B cells, are two key effector molecules in the humoral immune response. IgM exhibits a strong anti-infectious effect, while IgG participates in the phagocytosis of monocytes ( Zhang et al, 2021 ). T lymphocytes are important immune cells involved in the regulation of cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance of the subsequent compounds was measured at 440 nm (proline [Pro]) and 570 nm (all other amino acids). The molecular weight distribution of SePPs was determined following a previously reported method ( 13 ). Standard molecular weight samples of aprotinin (6500 Da), bacitracin (1422 Da), Gly-Gly-Tyr-Arg (451 Da), and reduced GSH (307 Da) were passed through a 0.22 μm filter and deposited in a Superdex 200 10/300 GL column.…”
Section: Methodsmentioning
confidence: 99%
“…According to Liu et al, selenium biofortified soy peptides could reduce CCl 4 -induced liver fibrosis by increasing GSH-Px activity and GSH content, improving hepatocyte survival, inhibiting hepatic stellate cell activation, and improving antioxidant capacity ( 12 ). Zhang et al observed that SePPs could regulate immunoglobulin (Ig)M, IgG, and IgA secretion, significantly increase splenic interleukin 2 (IL-2), interferon-gamma (IFN-γ), nitric oxide (NO), and cyclic guanosine monophosphate (cGMP) production, and IL-2, IFN-γ, and inducible NO synthase (iNOs) mRNA expression, as well as enhance host-specific and non-specific immunity via a cyclophosphamide-induced immunosuppression mice model ( 13 ). The beneficial effects of selenium-enriched peptides on health were confirmed previously, whereas, the protective mechanism of selenium-enriched peptides against heatstroke-induced liver injury is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to Met, a particular therapeutic interest has been attributed to selenium, an essential micronutrient, for its pleiotropic and immunomodulatory effects [11,12], as well as for its potent role in inhibition of expression of LPS induced proinflammatory cytokines [13]. It also enhances immunity and the function of cytotoxic effector cells and the production of antibodies [14,15].…”
Section: Introductionmentioning
confidence: 99%